PAPAN PARTIKEL AMPAS TEBU (Saccharum officinarum) DENGAN PEREKAT HIGH DENSITY POLYETHYLENE - Hasan, Abu; Yerizam, Muhammad; Kusuma, Mutmainnah Ningtyas (Politeknik Negeri Sriwijaya, 2020)
The problem regarding the availability of raw materials for the timber industry encourages research on the use of lignocellulosic materials to develop, one of which is bagasse. The large amount of bagasse and plastic waste that is not utilized as waste in the community makes it possible to carry out further processing into particle board. Plastic waste that can be used as an adhesive in the manufacture of particle boards is high density polyethylene (HDPE) plastic. The method used was Hand lay-up, which was arranging the pattern of bagasse fibers randomly and bidirectional crossed, the ratio of adhesive and bagasse fibers 70:30, compressed by varying the pressing time of 15, 30, 45, 60, 75 minutes 150 0C and a pressure of 100 kgf/cm2. The best results from the manufacture of particle board under 60 minutes of pressing, the bidirectional arrangement pattern has better physical and mechanical properties than the random arrangement pattern. Showed the values of crossed bidirectional fiber moisture content is 4,898%, density 0.64 g/cm3, swelling 8.15% , water absorption 21.71% , MOR 483.11 kgf/cm2 and MOE 1740.95 kgf/cm2.